2006
DOI: 10.1016/j.rapm.2006.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Iontophoretic Transdermal System for Acute-Pain Management After Orthopedic Surgery: A Comparative Study With Morphine Intravenous Patient-Controlled Analgesia

Abstract: Results of this study demonstrate fentanyl ITS and a standard regimen of morphine IV PCA were comparable methods of pain control for management of acute postoperative pain after THR, on the basis of the PGA success ratings and pain intensity in the first 24 hours of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 5 publications
1
57
0
1
Order By: Relevance
“…Similar satisfaction and pain intensity score reporting was repeated in further active-comparator studies (Table 1) (Viscusi et al 2004; Hartrick et al 2006; Minkowitz et al 2007). There were no significant differences in the rate of withdrawal of patients from these studies due to inadequate analgesia (around 10%–15% in both iv PCA and ITS groups).…”
Section: Efficacy Studiessupporting
confidence: 58%
“…Similar satisfaction and pain intensity score reporting was repeated in further active-comparator studies (Table 1) (Viscusi et al 2004; Hartrick et al 2006; Minkowitz et al 2007). There were no significant differences in the rate of withdrawal of patients from these studies due to inadequate analgesia (around 10%–15% in both iv PCA and ITS groups).…”
Section: Efficacy Studiessupporting
confidence: 58%
“…Fentanyl ITS 40 µg up to 6 doses/h316Up to 72 hFentanyl ITS equivalent to morphine IV PCA (patient global assessment of the method of pain control during the first 24 h)B. Morphine IV PCA (1 mg/dose) up to 10 doses/h320 Hartrick et al [8]OrthopedicA. Fentanyl ITS 40 µg up to 6 doses/h395Up to 72 hFentanyl ITS equivalent to morphine IV PCA (patient global assessment ratings of the method of pain control of either “excellent” or “good” in the first 24 h)B.…”
Section: Methodsmentioning
confidence: 99%
“…A second clinical trial was a randomized controlled comparison of the fentanyl iontophoretic system and an intravenous morphine pump in patients following major surgery and demonstrated that the noninvasive fentanyl system produced postsurgical pain control that was equivalent to that provided by the intravenous morphine pump [37]. Subsequent clinical trials demonstrated efficacy in controlling pain after orthopedic and gynecological surgery [38,39]. However, despite these encouraging results, the marketing authorization for Ionsys was suspended by the European Medicines Agency in 2009 following the identification of corrosion of one component in the system in one batch of the product; the authorization was not renewed.…”
Section: Physical Enhancement Strategiesmentioning
confidence: 99%